PENGARUH KETIDAKPUASAN DAN KEBUTUHAN MENCARI VARIASI TERHADAP PERPINDAHAN MEREK SMARTPHONE SAMSUNG KE MEREK SMARTPHONE LAIN DI WILAYAH SURABAYA - BASHORI, AHMAD (Jurnal Ilmu Manajemen (JIM), 2018)
This study aims to examine the influence of consumer dissatisfaction and variety seeking on brand switching Samsung Smartphone. Used as a sample 220 respondents drawn from Plaza Marina Surabaya and World Trade Center Surabaya. The sampling technique is non probability sampling using judgmental sampling method. Data analysis techniques using multiple linear regressions. The results showed that there is a positive and significant influence among consumer dissatisfaction and the need for finding variations against the transfer of Samsung smartphone brand to other smartphone brands. And the greatest influence among the variabels of dissatisfaction and the need to find the variation that attracts the greatest contribution is the influence of the need to look for hight consumer variation. Keywords : consumer dissatisfaction, variety seeking, brand switching behavior.